Factors Affecting the Financial Performance of the Food and Beverage Subsector on the Indonesian Stock Exchange - Marthaningrum, Fitrianna Chandra; Anggraeni, Muthia; Adini, Charity Putri; Alodia, Salwa Chandra; Leon, Farah Margaretha (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
Financial performance is an important factor for decision-making in companies. The aim of this research is to determine the effect of ownership concentration, operating efficiency and cash holdings on financial performance with control variables, namely company size, debt ratio and growth opportunities. The novelty in this research is the operating efficiency variable. Population that was used in this study are food and beverage companies listed on the Indonesia Stock Exchange for the period 2018 - 2022. The number of samples in this research was 22 companies. The method used in this research is panel data regression using the Eviews 9 application. The outcome from this research shows that ownership concentration has a significant positive value on financial performance and debt ratio as control variable has a significant negative value on financial performance. The expected benefits that will be obtained from this research is to increase insight into the influence of ownership concentration on financial performance, both for managers in managing individual or organizational ownership to improve financial performance and for investors as a consideration before spending their capital.